Effects of Alternative Feed Timing on Growth Performance and Water Usage of Growing Beef × Dairy Heifers Fed a High Roughage Diet - Clayton H. Stoskopf (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to evaluate the effects of feed delivery time on growth performance and water usage of growing cattle on high-roughage diets fed ad libitum during periods of heat stress. Study Description: A total of 260 black-hided, dairy-derived beef heifers were blocked by weight, stratified within block, and randomly assigned to 20, 13-head pens. Pens were randomly assigned to one of two treatments: 7:00 a.m. or 7:00 p.m. feed delivery of a diet formulated to provide 50 Mcal of net energy for gain per 100 lb of dry matter for ad libitum intake. Heifers were fed once daily, targeting 10% daily feed refusals for an 84-day period. Water usage was recorded using meters attached to each water unit. The Bottom Line: Delivering feed at 7:00 p.m. did not improve growth performance compared to 7:00 a.m. feedings, but the later feeding time did decrease water usage in growing heifers during an 84-day feeding period.
Keywords: heifers; feeding time; ad libitum